Yuriy Vitalijovych Sukhin - Orthopedic Traumatologists of Ukraine, Association of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is devoted to the 50th anniversary of the birth of the Honored Doctor of Ukraine, Doctor of Medical Sciences, professor, head of the Department of Traumatology and Orthopedics of the Odessa National Medical University, president of the Association of Orthopedic Traumatologists of the Odessa Region, a member of the Presidium of the Board of the Ukrainian Association of Orthopedic Orthopedic Traumatologists, a member of SICOT Sukhin Yu V.